Beyond nuclear thinking - Malcolmson, Robert W. (McGill-Queen's University Press, 1990)
Most of what is written on nuclear weapons concentrates, understandably, on the here and now: the nuclear threat is a central and continuing fact of modern history . But this is intellectually constricting, both for understanding the nuclear age and for making thoughtful political judgments. It is essential to recognize what we have inherited since 1945 and why people have thought about nuclear weapons in the way they have. In Beyond Nuclear Thinking, Robert Malcolmson analyses the development of nuclear weapons and nuclear strategy since 1945, connecting the legacies of the past with the politics of the 1990s. The nuclear nation states still consider it legitimate to use the threat of nuclear weapons to achieve their own ends. Malcolmson explains why the doctrine of "deterrence" became so central to the political idea of security and reveals the confused nature of recent approaches to the pursuit of international security. Beyond Nuclear Thinking presents a non-technical and broadly based interpretation of important aspects of life and thought in the nuclear age.